Pengaruh Bimbingan Kelompok Teknik Diskusi Terhadap Kematangan Karir - Karamoy, Yurike Kinanthy; Joti, Joti; Budiono, Arifin Nur (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
There are indications of low career maturity, especially among class VIII students. Often the negative impact of career maturity is more influenced by feelings that do not convince oneself to be able to progress further, this impact is influenced by the surrounding environment which is included in the low education category, thus having an impact on the next generation and the economy. These factors have quite a big influence on students to continue their wishes. The aim of this research is to determine the effect of discussion technique group guidance on the career maturity of class VIII students at SMPN 13 Jember. The research subjects were class VIII students at SMPN 13 Jember for the 2022/2023 academic year, totaling 32 students. Quantitative research with pre-experimental research methods (pre-experimental design). The sampling technique uses purposive sampling technique (with certain criteria). The population in this study were 33 class VIII students at SMPN 13 Jember and all of them were used as research samples. Data collection in this research used a questionnaire. The results of the research show that there is an influence of discussion technique group guidance on the career maturity of class VIII students at SMPN 13 Jember. Data analysis using the T test formula with the help of SPSS states that the calculated sig (2-tailed) value is 0.000. With these results Ha is accepted and H0 is rejected